Witnesses to the Witan? Some Unrecognized Legislative Idioms in Old English Verse. - Jurasinski, Stefan (Studies in Philology)
The article focuses on how Old English poetry provides overlooked insights into the legal and legislative practices of pre-Conquest England. Topics include the depiction of witan assemblies in verse, the contrast between poetic evidence and prevailing legal scholarship, and the reassessment of how royal laws were interpreted and applied in early medieval governance.